Fomes fomentarius and F. inzengae-A Comparison of Their Decay Patterns on Beech Wood - Cristini, Valentino; Nop, Patrik; Zlámal, Jan; Vand, Mojtaba Hassan; Šeda, Vít; Tippner, Jan (Microorganisms, 2023)
Wood-decaying fungi are responsible for the degradation of wood and the alteration in its material properties. Fomes fomentarius (L.) Fr. is one of the most common white-rot fungi colonising coarse wood and standing trees. In recent years, according to their genetic, physiological, and morphological differences, Fomes inzengae (Ces. and De Not.) Lécuru was identified as an independent species. This article aimed to compare the impact of the degradation caused by both species on the anatomical, physical, and mechanical properties of beech wood. When comparing the degradation caused by different strains of both species, no statistically significant difference was found in mass loss (ML) or moisture content (MC). A relevant correlation between ML and MC was confirmed for both species. Variabilities in the density distribution of the degraded and intact bending samples were found to be statistically different. No relevant difference was observed in the modulus of rupture (MOR) between the two species after each exposure period. A strong linear relationship between the MOR and the dynamic modulus of elasticity was revealed for both species. Both species showed decay patterns typical for simultaneous white rot and soft rot. According to the presented results, the impact of both species on the investigated material properties of wood cannot be considered significantly different.
Keywords: white rot; nondestructive testing; biodegradation; tree biomechanics; wood-decaying fungi; tree stability